African swine fever control and market integration in Ugandan peri-urban smallholder pig value chains: an ex-ante impact assessment of interventions and their interaction - Ouma, Emily A.; Dione, Michel M.; Birungi, Rosemirta; Lule, Peter M.; Mayega, L.; Dizyee, K. (Elsevier, 2018)
Pig production in peri-urban smallholder value chains in Uganda is severely constrained by impact of disease, particularly African swine fever (ASF), and the economic consequences of an inefficient pig value chain. Interventions in the form of biosecurity to control ASF disease outbreaks and pig business hub models to better link smallholder farmers to pig markets have the potential to address the constraints. However, there is a dearth of evidence of the effects of the interventions on performance and distribution of outcomes along the pig value chain. An ex-ante impact assessment utilising System Dynamics model was used to assess the impact of the interventions in peri-urban pig value chains in Masaka district. The results showed that although implementation of biosecurity interventions results in reduction of ASF outbreaks, it also leads to a 6.3% reduction in farmer profit margins per year but more than 7% increase in other value chain actors' margins. The pig business hub intervention alone results in positive margins for all value chain actors but minimal reduction in ASF outbreaks. When biosecurity and the pig business hub interventions are implemented together, the interaction effects of the interventions result in positive outcomes for both the control of ASF and improvement in farmers' margins. Farmers may therefore be unwilling to adopt biosecurity practices if implemented alone to control ASF outbreaks unless there is a corresponding financial incentive to compensate for the high costs. This has implications for policy or developing institutions to facilitate cost sharing arrangement among chain actors and/or third party subsidy to provide incentives for producers to adopt biosecurity measures.